CD11c+ cells primed with unrelated antigens facilitate an accelerated immune response to influenza virus in mice. Issue 2 (13th January 2014) - Richert, Laura E.; Rynda‐Apple, Agnieszka; Harmsen, Ann L.; Han, Soo; Wiley, James A.; Douglas, Trevor; Larson, Kyle; Morton, Rachelle V.; Harmsen, Allen G.
<x xml:space="preserve">Abstract</x> Recent evidence suggests that an individual's unique history and sequence of exposures to pathogens and antigens may dictate downstream immune responses to disparate antigens. We show that the i.n. delivery of nonreplicative virus‐like particles (VLPs), which bear structural but no antigenic similarities to respiratory pathogens, acts to prime the lungs of both C56BL/6 and BALB/c mice, facilitating heightened and accelerated primary immune responses to high‐dose influenza challenge, thus providing a nonpathogenic model of innate imprinting. These responses correspond closely to those observed following natural infection with the opportunistic fungus, Pneumocystis murina, and are characterized by accelerated antigen processing by DCs and alveolar macrophages, an enhanced influx of cells to the local tracheobronchial lymph node, and early upregulation of T‐cell co‐stimulatory/adhesion molecules. CD11c+ cells, which have been directly exposed to VLPs or Pneumocystis are necessary in facilitating enhanced clearance of influenza virus, and the repopulation of the lung by Ly‐6C+ precursors relies on CCR2 expression. Thus, immune imprinting 72 h after VLP‐priming, or 2 weeks after Pneumocystis‐priming is CCR2‐mediated and results from the enhanced antigen processing, maturation, and trafficking abilities of DCs and alveolar macrophages, which cause accelerated influenza‐specific primary immune responses and result in superior viral clearance.